The global menace of arsenic and its conventional remediation - A critical review. (September 2016) - Sarkar, Arpan; Paul, Biswajit
Abstract: Arsenic is a ubiquitous element found in the earth crust with a varying concentration in the earth soil and water. Arsenic has always been under the scanner due to its toxicity in human beings. Contamination of arsenic in drinking water, which generally finds its source from arsenic-containing aquifers; has severely threatened billions of people all over the world. Arsenic poisoning is worse in Bangladesh where As(III) is abundant in waters of tube wells. Natural occurrence of arsenic in groundwater could result from both, oxidative and reductive dissolution. Geothermally heated water has the potential to liberate arsenic from surrounding rocks. Inorganic arsenic has been found to have more toxicity than the organic forms of arsenic. MMA and DMA are now been considered as the organic arsenic compounds having the potential to impair DNA and that is why MMA and DMA are considered as carcinogens. Endless efforts of researchers have elucidated the source, behavior of arsenic in various parts of the environment, mechanism of toxicity and various remediation processes; although, there are lots of areas still to be addressed. In this article, attempts have been made to lay bare an overview of geochemistry, toxicity and current removal techniques of arsenic together. Highlights: Presence of arsenic in the groundwater has threatened the human health around the world. Dissolution of arsenic into the groundwater is influenced by various physicochemical and biological activities. Long term exposure to arsenic can cause cancer and other deadly diseases. It has been found that the As(III) is more toxic than the As(V). Various techniques have been employed to remediate arsenic from groundwater to make the water safe for drinking.